Pembentukan Kepribadian Peserta Didik Melalui Pendidikan Keluarga Islami - Syibromilisi Syibromilisi (Sekolah Tinggi Ilmu Tarbiyah Buntet Pesantren Cirebon, 2021)
Education is a very interesting issue for educators and mothers who are always dealing with children who need education. Parentingand raising children means maintaining life and health and educating them with sincerity and love. The purposes of this studyare 1) To determine the personality formation of students based on Islamic education. 2) To Know the nature of Islamic family education. 3) To find out the personality formation of students throughIslamic family education.The method used is book survey research or literature study, namely research on books, reading materials related to theoretical problemsandintheliteraturethathastodowithsourcesofstudyanddiscussionthatcanshowlogically related facts, in order to produce qualitative conclusions based on inductive, deductive, and convergence analysis.Based on the results of the discussion that: The formation of the personality of students based on Islamic education is as the main and first educator for the development of the potential of students, through getting used to reading the Qur'an, carrying out prayer lessons, praying before and after good activities. The essence of Islamic family education is through 1) Moral education both at home and at school, 2) Familiarize and train students to always have good morals, 3) Parents always set a good example and correct when students are wrong.Keyword:Personality Formation, Islamic Family Education. The conclusions of this study are that: Formation of the personality of students through Islamic family education, namely 1) Get used to doing things that are good and right. 2) Get in the habit of giving examples/examples. 3) Get used to giving guidance with patience and affection.